2014
DOI: 10.1179/2045772314y.0000000280
|View full text |Cite
|
Sign up to set email alerts
|

Neurological and functional recovery after thoracic spinal cord injury

Abstract: Objective: To describe neurological and functional outcomes after traumatic paraplegia. Design: Retrospective analysis of longitudinal database. Setting: Spinal Cord Injury Model Systems. Participants: Six hundred sixty-one subjects enrolled in the Spinal Cord Injury Model Systems database, injured between 2000 and 2011, with initial neurological level of injury from T2-12. Two hundred sixty-five subjects had second neurological exams and 400 subjects had Functional Independence Measure (FIM) scores ≥6 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
60
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 23 publications
3
60
2
2
Order By: Relevance
“…Performing assessments of self‐care ability not only identifies those older people who require support, but it can also enhance people's understanding of self‐care. Promoting self‐care ability can help prevent diseases, improve quality of life (Heidarzadeh, Atashpeikar, & Jalilazar, ), and aid in one's recovery from illness (Lee, Leiby, & Marino, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Performing assessments of self‐care ability not only identifies those older people who require support, but it can also enhance people's understanding of self‐care. Promoting self‐care ability can help prevent diseases, improve quality of life (Heidarzadeh, Atashpeikar, & Jalilazar, ), and aid in one's recovery from illness (Lee, Leiby, & Marino, ).…”
Section: Introductionmentioning
confidence: 99%
“…Promoting self-care ability can help prevent diseases, improve quality of life (Heidarzadeh, Atashpeikar, & Jalilazar, 2010), and aid in one's recovery from illness (Lee, Leiby, & Marino, 2016).…”
mentioning
confidence: 99%
“…Because of the retrospective nature of this study, more granular outcome measures, such as functional independence measure (FIM), were not available for analysis. Although the significance of AIS grade has been questioned in thoracic SCI, Lee and colleagues 51 recently showed that AIS grade changes are associated with significant functional benefit relative to FIM scores and ambulation in a retrospective analysis of a large longitudinal database of patients with thoracic SCI. 52 Structural MRI findings correlated with early impairment with varying resolution, depending on the scoring scheme (e.g., BASIC vs. sagittal grade).…”
Section: Discussionmentioning
confidence: 99%
“…11, 12 However, a substantial problem in translating pre-clinical findings from rodent models of SCI to human clinical trials is the fact that many experimental therapies for SCI use only moderate injury severity models, whereas most humans sustain severe injuries. 32,33 Severe injury models in rodents appear a priori to offer a more valuable tool for identifying therapies that could merit clinical translation. This article has been peer-reviewed and accepted for publication, but has yet to undergo copyediting and proof correction.…”
Section: Discussionmentioning
confidence: 99%
“…Second, taking advantage of the transient survival of allogeneic BMSC transplants, we examined whether BMSCs genetically engineered to over-express BDNF can further augment tissue sparing and functional recovery. To enhance clinical relevance, we used a model of severe T8 spinal cord compression because most human injuries are severe in degree; 32,33 BMSCs have not previously been tested in models of severe rodent SCI that are most likely to predict benefit in clinical trials, 34 and surprisingly BMSCs have gone on to human clinical trials without such supportive rodent data. We now report that subacute implants of allogeneic BMSC grafts to sites of severe SCI fail to improve motor or autonomic outcomes, suggesting that their local administration is unlikely to merit clinical translation.…”
mentioning
confidence: 99%